Structural design of polymer protective coatings for reinforced concrete structures. Part I: Theoretical considerations - Kamaitis, Zenonas (Journal of Civil Engineering and Management, 2007)
In a number of situations reinforced concrete structures must be protected by barrier materials to prevent contact with aggressive agents. One of the ways to protect concrete structures from corrosion is to use protective polymer coatings. Polymers as coating materials are not totally resistant and impermeable to all aggressive agents. Gases, vapors and liquids penetrate into a polymer so that the polymer mass swells and eventually disintegrates. However, the penetration/disintegration progresses at a much lower rate than that in the concrete. Surface coatings are able to reduce considerably the penetration, to slow down the rate of deterioration of concrete cover and to overcome most durability problems associated with external attack. In this article the mechanism of degradation of polymer coatings are analyzed. Methodology and predictive models for the degradation over time caused by aggressive actions of polymer coatings are presented. Proposed models can be applied to design of polymer coatings. Such a design of coatings is presented in a simple form for engineering design purposes.Gelžbetoninių konstrukcijų polimerinių apsauginių dangų projektavimas. I dalis. Teorinė samprataSantrauka. Agresyviojoje aplinkoje eksploatuojamos gležbetoninės konstrukcijos turi būti apsaugotos nuo irimo. Vienas iš būdų yra polimerinės apsauginės dangos. Polimerai nėra absoliučiai atsparūs ir nelaidūs visoms agresyviosioms aplinkoms. Tačiau degradacijos procesai polimeruose yra gerokai lėtesni nei betone. Prognozuoti šiuos procesus labai svarbu, norint teisingai parinkti dangų parametrus bei užtikrinti konstrukcijų, eksploatuojamų agresyviojoje aplinkoje, patikimumą. Straipsnyje analizuojama polimerinių dangų degradacija. Pateikta degradacijos procesų klasifikacija (1 lentelė) ir jų matematiniai modeliai. Polimerinių dangų vertinimą siūloma formuluoti keturiais ribiniais būviais, naudojant deterministinį ar tikimybinį skaičiavimą ((27), (28) ir (29) formulės). Pateikti ribiniai būviai gali būti naudojami projektuojant gelžbetoninių konstrukcijų apsaugines dangas.Reikšminiai žodžiai: gelžbetoninės konstrukcijos, korozija, polimerinės dangos, fizinis ir cheminis atsparumas, difuzija, adhezija, projektavimas.First Published Online: 14 Oct 2010